2022
DOI: 10.1021/acs.cgd.2c00520
|View full text |Cite
|
Sign up to set email alerts
|

Amide-Driven Secondary Building Unit Structural Transformations between Zn(II) Coordination Polymers

Abstract: The behavior of coordination polymers (CPs) against external stimuli has witnessed remarkable attention, especially when the resulting CPs present reversible molecular arrays. Accordingly, CPs with these characteristics can lead to differences in their properties owing to these structural differences, being promising for their use as potential molecular switches with diverse applications. Herein, we have synthesized four Zn(II) CPs bearing α-acetamidocinnamic acid (HACA) and 4,4′-bipyridine (4,4′-bipy). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 104 publications
4
6
0
Order By: Relevance
“…Although this event is rather rare, there are some reports about it. In a few interesting cases, supramolecular isomers were formed in the reaction vessel concomitantly. Although structural transformation of CPs in the solid phase is highly regarded, there are few studies on the structural transformation in the liquid phase in CPs, especially through dissolution–recrystallization structural transformation (DRST). ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this event is rather rare, there are some reports about it. In a few interesting cases, supramolecular isomers were formed in the reaction vessel concomitantly. Although structural transformation of CPs in the solid phase is highly regarded, there are few studies on the structural transformation in the liquid phase in CPs, especially through dissolution–recrystallization structural transformation (DRST). ,,, …”
Section: Introductionmentioning
confidence: 99%
“… 44 47 Although structural transformation of CPs in the solid phase is highly regarded, 48 56 there are few studies on the structural transformation in the liquid phase in CPs, especially through dissolution–recrystallization structural transformation (DRST). 23 , 28 , 36 , 57 60 …”
Section: Introductionmentioning
confidence: 99%
“…Herein, the spectra are broad without vibronic progressions. According to previous reports about polynuclear Cu­(I) clusters, ,,, the observed emission can be assigned to the metal-to-ligand (d 10 Cu → π* dppy) charge-transfer (MLCT) state.…”
Section: Resultsmentioning
confidence: 65%
“…To date, it is still difficult to accurately predict the target structure of mixed-ligand-based multicore coordination complexes under the current crystallization techniques, mainly owing to the lack of a deeper understanding of the crystal growth process and various experimental parameters that influence their structures. Therefore, identifying the crystal structures of thermodynamic and dynamic products as well as the structural transformation process could provide important hints for the controllable synthesis of functional multicore coordination compounds. …”
Section: Introductionmentioning
confidence: 99%
“…To date, only one dihydrate and one cocrystal have been reported. The dihydrate structure connected the HACA molecules through masked synthons of water clusters supported by acid···amide interactions, , whereas the cocrystal contained 2-pyridone (Pdon), presenting Pdon···acid and amide···amide synthons . However, previous studies performed in the group with coordination compounds suggested a tendency of the HACA molecules toward being ordered by amide···amide patterns, leading to supramolecular chains or cycles depending on the synthetic conditions. …”
Section: Introductionmentioning
confidence: 99%